Speech Acts in EFL Classrooms - Christianto, Danin (Journal of Pragmatics Research, 2020)
Speech act is a functional unit in the form of an act which helps humans understand or accomplish things with words in communication. This research was aimed to find out and analyse the types of speech acts which were performed by teachers and students in English as a Foreign Language (EFL) classrooms. The researcher employed the speech act theory from Cruse (2000) to analyse and interpret the research results. Qualitative research was applied in this research due to the data source was from the teaching and learning activities in naturalistic environments in English classrooms. The subjects of this research were teachers and students in REAL Equivalent English classrooms. The results showed that there were three types of speech acts found in the interactions between the teachers and students, namely locutionary act, illocutionary act, and perlocutionary act. Locutionary act was performed when teachers and students uttered expressions with no certain intentions. Illocutionary act, on the other hand, was performed when the expressions contained certain intentions to listeners. Perlocutionary act was performed when the listeners showed responses and acted as feedback to the speakers’ utterances. By conducting this research, the researcher hopes that it can give more insights to readers regarding to the study of speech act theory in pragmatics field. Keywords:   English as a Foreign Language (EFL) Classrooms, Speech Acts, REAL Equivalent English, Teachers and Students.